Predictors of fluid intravasation during operative hysteroscopy: a preplanned prospective observational study with 200 cases - Márlon de Freitas Fonseca; Claudio Moura Andrade Junior; Eduardo de Almeida Nogueira; Felipe Ventura Sessa; Claudio Peixoto Crispi (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2015)
PURPOSE: To verify the predictors of intravasation rate during hysteroscopy. METHODS: Prospective observational study (Canadian Task Force classification II-1). All cases (n=200 women; 22 to 86 years old) were treated in an operating room setting. Considering respective bag overfill to calculate water balance, we tested two multiple linear regression models: one for total intravasation (mL) and the other for absorption rate (mL.min-1). The predictors tested (independent variables) were energy (mono/bipolar), tube patency (with/without tubal ligation), hysterometry (cm), age≤50 years, body surface area (m2), surgical complexity (with/without myomectomy) and duration (min). RESULTS: Mean intravasation was significantly higher when myomectomy was performed (442±616 versus 223±332 mL; p<0.01). In the proposed multiple linear regression models for total intravasation (adjusted R2=0.44; p<0.01), the only significant predictors were myomectomy and duration (p<0.01).In the proposed model for intravasation rate (R2=0.39; p<0.01), only myomectomy and hysterometry were significant predictors (p=0.02 and p<0.01, respectively). CONCLUSIONS: Not only myomectomy but also hysterometry were significant predictors of intravasation rate during operative hysteroscopy.